2015
DOI: 10.1586/17474086.2015.1049593
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-induced programmed cell death in the pathogenesis of acquired aplastic anemia

Abstract: The mechanism of acquired aplastic anemia (AA), a bone marrow hematopoiesis failure disease, has not been fully understood. TNF-α is a pleiotropic cytokine involved in cell proliferation, differentiation and death, and inflammation through binding to specific receptors on cell membranes. Aberrant secretion of TNF-α contributes to a number of human diseases, including tumor development and inflammation. TNF-α is also an important negative regulator of hematopoiesis. Over-expression of TNF-α not only directly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…It has been proposed that both IFNγ and TNFα contribute to hematopoietic repression in the pathogenesis of AAA. [17][18][19]28,29 The elevated serum levels of both IFNγ and TNFα are consistent with the occurrence of BMF in our animal model (Online Supplementary Figure S15). However, we determined that these two inflammatory cytokines function in opposite ways in the pathogenesis of AAA.…”
Section: Cd4supporting
confidence: 83%
See 2 more Smart Citations
“…It has been proposed that both IFNγ and TNFα contribute to hematopoietic repression in the pathogenesis of AAA. [17][18][19]28,29 The elevated serum levels of both IFNγ and TNFα are consistent with the occurrence of BMF in our animal model (Online Supplementary Figure S15). However, we determined that these two inflammatory cytokines function in opposite ways in the pathogenesis of AAA.…”
Section: Cd4supporting
confidence: 83%
“…TNFα is thought to be a key mediator of autoimmune BMF. 28,29 However, inactivation of TNFα signaling surprisingly accelerates the progression of BMF in Tak1 mut mice, an observation which runs counter to generally accepted theory. The BMF phenotypes of Tak1 mut and Tak1 mut Tnfr -/-mice (deletion of both TNF receptor 1 and 2) resemble most of the clinical manifestations seen in chronic and severe AAA patients, respectively.…”
Section: 24mentioning
confidence: 76%
See 1 more Smart Citation
“…Multiple studies have demonstrated that TNF- α inhibits erythropoiesis and causes anemia in human. 34, 38, 39, 40, 41 Moreover, TNF- α can induce cell death of erythroid cells via caspase-mediated cleavage of the master regulator of erythropoiesis, GATA1. 9, 15, 42, 43, 44 Our finding that Stk40 deletion in the fetal liver causes aberrant activation of TNF- α signaling supports the idea that Stk40 plays an important role in repressing TNF- α signaling activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammatory signaling is critical during infection and inflammation, prolonged exposure to inflammatory signals including TLRs, IFNs, TNF, and IL-1 will repress the self-renewal of HSCs, which eventually results in HSC exhaustion [46,51,59,60,74,102]. Indeed, myelodysplastic syndromes (MDSs) and BMF syndromes have been associated with excessive TNF and IFNγ signaling, both of which have been proposed to contribute to the repression of hematopoietic cells [57,61,66,103].…”
Section: Necroinflammation and Bmfmentioning
confidence: 99%